2022
DOI: 10.1038/s41598-022-17241-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive immunity against SARS-CoV-2 N protein in Central and West Africa precedes the COVID-19 pandemic

Abstract: Early predictions forecasted large numbers of severe acute respiratory syndrome coronavirus (SARS-CoV-2) cases and associated deaths in Africa. To date, Africa has been relatively spared. Various hypotheses were postulated to explain the lower than anticipated impact on public health in Africa. However, the contribution of pre-existing immunity is yet to be investigated. In this study, the presence of antibodies against SARS-CoV-2 spike (S) and nucleocapsid (N) proteins in pre-pandemic samples from Africa, Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Our antibody data suggests pre-existing coronavirus immunity with 10.4% (14/134) of HCWs and 20% (23/115) of individuals in the general population who only had SARS-CoV-2 N antibodies prior to vaccination. These results recapitulate other studies highlighting a similar phenomenon (11,18,26). SARS-CoV-2 N seropositivity could suggest undocumented infections with other as yet unrecognized coronaviruses, including animal coronaviruses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our antibody data suggests pre-existing coronavirus immunity with 10.4% (14/134) of HCWs and 20% (23/115) of individuals in the general population who only had SARS-CoV-2 N antibodies prior to vaccination. These results recapitulate other studies highlighting a similar phenomenon (11,18,26). SARS-CoV-2 N seropositivity could suggest undocumented infections with other as yet unrecognized coronaviruses, including animal coronaviruses.…”
Section: Discussionsupporting
confidence: 91%
“…The vast majority of antibody studies have utilized ELISA assays to recombinant SARS CoV-2 antigens. Multiple studies now indicate reduced specificity of these assays when analyzing samples originating from sub-Saharan Africa (11,18). Of note, our study employed virion based immunoblot which All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Specific antibodies against SARS-CoV-2 proteins in sera collected in sub-Saharan African regions before the emergence of SARS-CoV-2 in China have already been reported by other studies, with higher serological cross-reactivity to SARS-CoV-2 in sub-Saharan African regions than elsewhere [ 21 , 22 ], and sometimes attributed to higher exposure to human seasonal coronaviruses (HCoVs) in these regions [ 23 ].…”
Section: Discussionmentioning
confidence: 82%
“…After screening 38 studies (Figure 1) and excluding 16 (Supplementary references), 22 studies were eligible (18 retrieved from the main search and another 4 retrieved from cited/citation searches). 3-14, 22-31 19 studies were published in peer-reviewed journals and 3 were preprints. Other studies screened in-depth and excluded are shown in Supplementary References along with the reason for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Impetus for this hypothesis has been provided by several studies documenting humoral immunity to SARS-CoV-2 in African samples that predate the pandemic years. 3-12 This pattern has typically not been seen in populations from highly developed countries and its provenance remains elusive. This detected immunity does not seem to represent cross-reactivity of immune responses to known endemic coronaviruses that are extremely widely, practically ubiquitously, distributed across all continents.…”
Section: Introductionmentioning
confidence: 99%